ASPEK HUKUM INTERNASIONAL MILITERISASI DI RUANG ANGKASA (STUDI KASUS MILITERISASI RUANG ANGKASA OLEH AMERIKA SERIKAT) - Sigi, Immanuel; Kusuma, Zulfikar Jaya; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In 2019 The United Stetes creates a space force command that called as The United States Space Command the purposes are to empower capabilities of United States military so it can prevent or support future conflict.By legitimating its action on national security purpose it is appeared new issues on others country about their right of using outer space. This type of research can be classified as normative legal research Legal research is carried out by examining library material or mere secondary data.As a results of the research problem, there are the main things that can be considered. First, uridical studies on militarization of space according to international law has not regulated comprehensively on international sistem. However, every country prohibited to place or instal on the orbit or arround the earth or on celestial body of anything that could carrying nuclear weapons. Beside that, every country incorporated in the agreement is prohibited from forming military bases, forming installations and testing all types of weapons and military maneuvering behavior on celestial bodies.United Statess authority on establishing, developing, dan conducting militarization of space are contradicted on many Resolutions that adopted and made by the United Nations and international treaties. American violations of many Resolutions adopted and made by the United Nations and international treaties are a form of inconsistency of the United States on its role to maintain world stability and security.Keyword :Militerisation, Outer space, Security.